2016
DOI: 10.1111/bjop.12230
|View full text |Cite
|
Sign up to set email alerts
|

What Stroop tasks can tell us about selective attention from childhood to adulthood

Abstract: A rich body of research concerns causes of Stroop effects plus applications of Stroop. However, several questions remain. We included assessment of errors with children and adults (N = 316), who sat either a task wherein each block employed only trials of one type (unmixed task) or where every block comprised of a mix of the congruent, neutral, and incongruent trials. Children responded slower than adults and made more errors on each task. Contrary to some previous studies, interference (the difference between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 95 publications
1
20
0
1
Order By: Relevance
“…Corresponding to previous findings (Davies et al, 2004;Rueda, Posner, Rothbart, & Davis-Stober, 2004;Wright, 2017;Wright et al, 2003), our study observed the decreasing SRC effects of S-R and S-S conflict processing from children to adolescents and adults, suggesting that the Simonspatial-Stroop task provided a robust measurement of the SRC effect. The poorer performance of young participants due to the delayed maturation of anterior cingulate cortex (ACC) and dorsal lateral prefrontal cortex (dlPFC), which are involved in conflict monitoring and conflict resolution, respectively (Botvinick, Braver, Barch, Carter, & Cohen, 2001;Davies et al, 2004;Hämmerer et al , 2014;Rueda et al, 2004).…”
Section: Discussionsupporting
confidence: 90%
“…Corresponding to previous findings (Davies et al, 2004;Rueda, Posner, Rothbart, & Davis-Stober, 2004;Wright, 2017;Wright et al, 2003), our study observed the decreasing SRC effects of S-R and S-S conflict processing from children to adolescents and adults, suggesting that the Simonspatial-Stroop task provided a robust measurement of the SRC effect. The poorer performance of young participants due to the delayed maturation of anterior cingulate cortex (ACC) and dorsal lateral prefrontal cortex (dlPFC), which are involved in conflict monitoring and conflict resolution, respectively (Botvinick, Braver, Barch, Carter, & Cohen, 2001;Davies et al, 2004;Hämmerer et al , 2014;Rueda et al, 2004).…”
Section: Discussionsupporting
confidence: 90%
“…To measure verbal and non-verbal interference control: interference suppression, the Stroop effect was used for the verbal Stroop task, while the conflict effect was used for the non-verbal Global-Local task. The Stroop effect is the RT difference between incongruent trial types (pure block) and congruent (neutral) trial types (pure block) (Yow and Li, 2015;Wright, 2017). The conflict effect is the RT difference between incongruent local trials (pure block) and congruent (neutral) local trials (pure block) (Hofweber et al, 2020).…”
Section: Measures Of Cognitive Control Processesmentioning
confidence: 99%
“…Emotional Stroop tasks are widely used neuropsychological tools for the study of AB in addiction (Field et al, 2009). They are based on the classic colour Stroop task, which is used to measure selective attention (Wright, 2017). In classic Stroop tasks, participants are instructed to name the colour in which I can't get it off my mind: Attentional bias in former and current cocaine addiction colour names are written.…”
Section: Introductionmentioning
confidence: 99%